Mode I interlaminar fracture toughness behavior and mechanisms of bamboo. (5th December 2019) - Chen, Qi; Dai, Chunping; Fang, Changhua; Chen, Meiling; Zhang, Shuqin; Liu, Rong; Liu, Xianmiao; Fei, Benhua
Abstract: Bamboo, with its fast growth rate and outstanding mechanical properties, has received increasing attention as a green material for engineering applications. Compared to other mechanical properties, little is known about fracture toughness, especially the toughening mechanism of bamboo. In this study, the Mode I interlaminar fracture toughness of bamboo with different proportions of fiber cells (FCs) and parenchyma cells (PCs) was tested, using in situ SEM to investigate the intrinsic mechanisms and extrinsic mechanisms at the cellular level. The results showed that both initiation and crack growth energies of high fiber density region were the lowest, and the crack growth energy of middle fiber density region was the highest. The intrinsic toughening in bamboo is associated with plastic zone size and crack kinking which are governed by PCs. The extrinsic toughening is related to fiber bridging which is governed by FCs. Having the highest fracture toughness, the middle region of bamboo may be the best choice of natural fiber for manufacturing high performance green composite materials. This work fills the gaps in the knowledge of fracture toughness and mechanisms of bamboo, which is vital to the utilization of bamboo in the structural applications. Graphical abstract: Unlabelled Image Highlights: Initiation energy and crack-growth energy of bamboo are lowest in the region with highest fiber content. The highest growth-energy occurs in the middle region with a balanced content of fiber and parenchyma cells. Initiation energy is related to the intrinsic toughening mechanism through the plastic zoning and crack kinking. Crack-growth energy is associated with the extrinsic toughening mechanism via fiber bridging.